Peranan Dinas Tenaga Kerja dan Sertifikasi Kompetensi (DTKSK) Dalam Penyelesaian Perselisihan Hubungan Industrial Melalui Mediasi di Kota Denpasar - Anak Agung Alit Ista Damayanti; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
The Denpasar City Manpower and Competency Certification Office (DTKSK) is a government agency that has the function of fostering, controlling and supervising in the field of labor. However, in reality there are still many cases of industrial relations disputes. This study examines two problems, namely how the role of DTKSK Denpasar City in optimizing the settlement of industrial relations disputes through mediation and what are the inhibiting factors and efforts made by DTKSK Denpasar City in resolving industrial relations disputes through mediation? "The method used is an empirical law method and sourced from primary data and secondary data. This research is located at DTKSK Denpasar City. The technique in determining the sample uses non probability sampling with purposive sampling technique. In collecting data, document study techniques and interview techniques were used. Data analysis was carried out in a qualitative descriptive manner. Based on the results of the study, DTKSK Denpasar City has not run optimally in resolving industrial relations disputes because the number of industrial relations disputes that occur is not proportional to the number of mediators available at the Department of Labor and Competency Certification."